Telegram-Based Design of Automatic Plant Watering System - Sudimanto, Sudimanto; Setiawan, Dhanny; Christian, Marcel; Hidayat, Rokhman (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Regular watering is a very important activity in plant maintenance because plants need water to carry out photosynthesis and obtain the nutrients necessary to grow and develop properly. An automatic watering tool has been designed that can perform watering commands remotely. This automatic watering instrument is achieved by using a soil moisture sensor to measure the water content or soil moisture and a DHT22 sensor that can detect air temperature and humidity. Soil moisture information is sent via Telegram, using the Telegram bot feature on this automatic plant watering tool, so that the tool can be controlled remotely. This plant monitoring can save time and energy and maintain plant quality more effectively. Plant conditions can also be checked periodically to ensure that the plant's water needs are being properly met. This automatic plant watering solution therefore has the potential to increase productivity and efficiency in case of irregular watering of the plants.